Sosialisasi Hukum Pencegahan Tindak Pidana Asusila di Desa Cineumbeuy Kuningan - Royvaldo; Dadan Hermansyah; Holillah Romdhona; Wulan Cahyaningsih; Sopia Rahma; Haris Budiman; Suwari Akhmaddhian; Iman Jalaludin Rifai (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
The development of modern society has led to the development of crime which includes types and dimensions that did not previously exist. The more modern society is, the more modern the methods, techniques and methods of crime committed by the perpetrators. Society in general views decency as a form of deviation or crime, because it is contrary to the laws and norms that exist in society. Legal protection for child victims of sexual crimes in abstract form is regulated, among other things, in the Criminal Code. Formulation of moral crimes in the Criminal Code which can be used as a basis for ensnaring perpetrators. Implementation of legal education activities for the community of Cineumbeuy Village to increase community knowledge regarding the dangers of immoral crimes. The event was held in Cineumbeuy Village, Lebakwangi District, Kuningan Regency, precisely at the Cineumbeuy Village Multipurpose Building. In an effort to realize the principles of the rule of law in social and state life, the role and function of advocates as a free, independent and responsible profession is important, alongside judicial institutions and law enforcement agencies such as the police and prosecutors. Through the legal services provided, advocates carry out their professional duties to uphold justice based on the law for the benefit of the justice-seeking community, including efforts to empower the community to realize their fundamental rights before the law. The obligation to defend and provide legal assistance to poor people or groups by the lawyer profession is in line with the principles of justice for all and equality before the law and the right to be accompanied by an advocate without exception.